Deficiencies of Myeloid Differentiation Factor 88, Toll-Like Receptor 2 (TLR2), or TLR4 Produce Specific Defects in Macrophage Cytokine Secretion Induced by Helicobacter pylori - Obonyo, Marygorret (American Society for Microbiology, 2007)
Helicobacter pylori is a gram-negative microaerophilic bacterium that colonizes the gastric mucosa, leading to disease conditions ranging from gastritis to cancer. Toll-like receptors (TLRs) play a central role in innate immunity by their recognition of conserved molecular patterns on bacteria, fungi, and viruses. Upon recognition of microbial components, these TLRs associate with several adaptor molecules, including myeloid differentiation factor 88 (MyD88). To investigate the contribution of the innate immune system to H. pylori infection, bone marrow-derived macrophages from mice deficient in TLR2, TLR4, TLR9, and MyD88 were infected with H. pylori SS1 and SD4 for 24 or 48 h. We demonstrate that MyD88 was essential for H. pylori induction of all cytokines investigated except alpha interferon (IFN-α). The secretion of IFN-α was substantially increased from cells deficient in MyD88. H. pylori induced interleukin-12 (IL-12) and IL-10 through TLR4/MyD88 signaling. In addition, H. pylori induced less IL-6 and IL-1β in TLR2-deleted macrophages, suggesting that the MyD88 pathway activated by TLR2 stimulation is responsible for H. pylori induction of the host proinflammatory response (IL-6 and IL-1β). These observations are important in light of a recent report on IL-6 and IL-1β playing a role in the development of H. pylori-related gastric cancer. In conclusion, our study demonstrates that H. pylori activates TLR2 and TLR4, leading to the secretion of distinct cytokines by macrophages.